Prevalence of under nutrition among under-5 children in the urban field practice area of a medical college in Muzaffarnagar, Uttar Pradesh - Farooq, Umer; Sharma, Sangeeta J.; Raghav, Santosh (International Journal Of Community Medicine And Public Health, 2023)
Background: In India, undernutrition in children mal the age of five is a serious public health issue. Despite India's expanding economy, both urban and rural areas still have significant rates of undernutrition-related child mortality. There are hardly many studies that concentrate on cities. In order to determine the prevalence of undernutrition in the urban field practice area of a medical college in Muzaffarnagar, Uttar Pradesh, the current study was conducted. Objective of the study was using World Health Organization (WHO) growth standards, to determine the prevalence of undernutrition among children under the age of five. Methods: A community-based cross-sectional study was conducted in the urban field practice region of the medical college Muzaffarnagar, India, from August 2022 to November 2022. From 1875 registered families, 400 under-five-year-old children were randomly chosen, and a house-to-house survey was used to collect the study's data. The study's goals were explained to the parents, and their written agreement was obtained. The children who were accessible during the study period had their anthropometric measurements taken in accordance with WHO criteria. For nutritional deficits and other morbidities, the kids were checked. Data analysis was performed using the statistical package for the social sciences (SPSS) 23 programme and the Chi square test. Results: A total of 400 under 5 were examined by going from house to house, and 257 (64.2%) of them were underweight. Boys had significantly (p=0.001) more undernutrition than girls. In the age range of 49 to 60 months, it peaked. Conclusions: Children's malnutrition continues to be a problem for public health, especially among underprivileged populations.